Optimization and Prediction of Process Parameters in SPIF that Affecting on Surface Quality Using Simulated Annealing Algorithm - Baden, Aqeel Sabree (Al-Khwarizmi Engineering Journal, 2017)
Incremental sheet metal forming is a modern technique of sheet metal forming in which a uniform sheet is locally deformed during the progressive action of a forming tool. The tool movement is governed by a CNC milling machine. The tool locally deforms by this way the sheet with pure deformation stretching. In SPIF process, the research is concentrate on the development of predict models for estimate the product quality. Using simulated annealing algorithm (SAA), Surface quality in SPIF has been modeled. In the development of this predictive model, spindle speed, feed rate and step depth have been considered as model parameters. Maximum peak height (Rz) and Arithmetic mean surface roughness (Ra) are used as response parameter to assess the surface roughness of incremental forming parts along and across tool path direction. The data required has been generate, compare and evaluate to the proposed models that obtained from SPIF experiments.Simulated Annealing Algorithm (SAA) is utilized to develop an effective mathematical model to predict optimum level. In simulated algorithm (SA), an exponential cooling schedule depending on Newtonian cooling process is used and by choosing the number of iterations at each step on the experimental work is done. The SA algorithm is used to predict the forming parameters (speed, feed and step size) on surface quality in forming process of Al 1050 based on Taguchi‘s orthogonal array of L9 and (ANOVA) analysis of variance were used to find the best factors that effect on  the surface quality.